The witch's curse - Quinn, Jordan (Quinn, Jordan. Kingdom of Wrenly, 2014)
"It's been raining non-stop for six whole days. Someone has cursed the Kingdom of Wrenly. Can Lucas and Clara figure out who's behind the evil spell and stop the villain before it's too late?"--